#TITLE_ALTERNATIVE# - STEVEN (NIM. 10205036) : pembimbing ; Dr. Alamta Singarimbun , TJUNG
Reservoir modeling takes several parameters that support the results of the modeling which is consistent with the existing data in the real field. These parameters are related to the nature of rock and fluid characteristics that exist in the reservoir. The meaning of the reservoir here is petroleum reservoir. With these parameters applied into the equation of fluid flow, one will be obtained pressure distribution calculated numerically. The numerical method is finite difference method. Finite difference approximation is used only first derivatives. Approximation is obtained from a numerical representation of the fluid flow equation that has the form of partial differential equations. Finite difference approximation is terminated by an implicit method in the form of sparse matrix. By utilizing the matrix inversion calculation one will be obtained the transient pressure and with this pressure can be calculated how the rate of production of petroleum in a reservoir block that have wells. Furthermore, the rate of production can be used to predict when a production well can no longer produce oil.